2017
DOI: 10.1111/jace.15389
|View full text |Cite
|
Sign up to set email alerts
|

Reversible luminescence modulation of Ho‐doped K0.5Na0.5NbO3 piezoelectrics with high luminescence contrast

Abstract: A significant luminescence modulation behavior based on photochromic reactions was observed in Ho3+‐doped (Na0.52K0.48)0.92Li0.08NbO3 ceramics, fabricated by the conventional solid‐state reaction method. Under visible light irradiation (407 nm) for 20 second, the samples changed pale gray from initial pale green, and returned to their original color by a thermal stimulus of 230°C for 10 minutes, showing typical photochromic phenomenon. Under 453 nm excitation, the samples exhibited strong green emission at 551… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 37 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…Additionally, the generation of impurity phases can be due to the volatilization of alkali metal ions (K þ /Na þ ) in the high-temperature sintering environment (i.e., 1205 ○ C for 4 h) and then the stoichiometric deviation. [22][23][24] From the perspective of crystal symmetry, compared with the orthorhombic phase of pure KNN, the tetragonal phase of xEu-KNNBST is closer to cubic one, benefitting in reducing optical anisotropy and light scattering. Therefore, the optical transmittances of the xEu-KNNBST ceramics significantly improve.…”
Section: Phase and Microstructurementioning
confidence: 99%
“…Additionally, the generation of impurity phases can be due to the volatilization of alkali metal ions (K þ /Na þ ) in the high-temperature sintering environment (i.e., 1205 ○ C for 4 h) and then the stoichiometric deviation. [22][23][24] From the perspective of crystal symmetry, compared with the orthorhombic phase of pure KNN, the tetragonal phase of xEu-KNNBST is closer to cubic one, benefitting in reducing optical anisotropy and light scattering. Therefore, the optical transmittances of the xEu-KNNBST ceramics significantly improve.…”
Section: Phase and Microstructurementioning
confidence: 99%
“…15 In our previous studies, we found that KNN-based ceramics are very sensitive to visible light irradiation, showing a typical photochromism. 16,17 This photochromic behavior no doubt would bring about strong light scatting in transparent ferroelectric ceramics, which is very important for deeper understanding of such photo-induced scattering performance. However, there are only a few studies on the light scattering effect from photochromic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The rare‐earth (RE) ions–doped ferroelectric ceramics is becoming an interesting field because of the coupling of luminescence and electrical properties . Many ferroelectric ceramics doped with RE ions show efficient PL properties while maintaining their excellent electrical properties, making them multifunctional materials .…”
Section: Introductionmentioning
confidence: 99%
“…The rare-earth (RE) ions-doped ferroelectric ceramics is becoming an interesting field because of the coupling of luminescence and electrical properties. [1][2][3][4] Many ferroelectric ceramics doped with RE ions show efficient PL properties while maintaining their excellent electrical properties, making them multifunctional materials. [5][6][7] It is generally believed that the optimal properties of ferroelectric ceramics can be achieved under condition of multiphase coexistence, 8 such as morphotropic phase boundary (MPB).…”
Section: Introductionmentioning
confidence: 99%